Religion and the self in antiquity - Brakke, David; Satlow, Michael L.; Weitzman, Steven (Indiana University Press, 2005)
Shifting selves in late antiquity / Patricia Cox Miller -- The search for the elusive self in texts of the Hebrew Bible / Saul M. Olyan -- The slave self / J. Albert Harrill -- Prayer of the queen : Esther's religious self in the Septuagint / Esther Menn -- Giving for a return : Jewish votive offerings in late antiquity / Michael L. Satlow -- The self in Artemidorus' interpretation of dreams / Peter T. Struck -- Sensory reform in Deuteronomy / Steven Weitzman -- Locating the sensing body : perception and religious identity in late antiquity / Susan Ashbrook Harvey -- Dialogue and deliberation : the sensory self in the hymns of Romanos the Melodist / Georgia Frank -- From master of wisdom to spiritual master in late antiquity / Guy G. Stroumsa -- The beastly body in rabbinic self-formation / Jonathan Schofer -- Making public the monastic life : reading the self in Evagrius Ponticus' talking back / David Brakke -- The student self in late antiquity / Edward Watts